Clicking for a cause : using social media campaigns to drive awareness for golf tournaments and charitable organizations - Hambrick, Marion E.; Mahoney, Tara Q.; Calabrese, Rich (London : Human Kinetics, Inc., 2012)
Sport industry leaders have recognized the popularity of social media; however, some have struggled with quantifying the benefits of such usage (Fisher, 2009). This case explores the potential opportunities social media sites can provide to sport organizations. Golf tournament organizer TampaTourneys, LLC created an administrative Facebook page to keep its Facebook users informed about events. The organization also used the page to promote a cause related marketing campaign benefitting a charitable fundraiser. Partnering with Blackhawk Computers, TampaTourneys initiated a week-long campaign, which encouraged the tournament organizer's Facebook fans to tell their respective Facebook friends about the fundraiser and become fans of the TampaTourneys Facebook page. In turn, the organization made a monetary donation on behalf of its current and new fans. Based on the campaign's success, TampaTourneys decided to initiate a second and longer fundraising effort. The case asks students to analyze data collected from the first fundraising campaign and develop a new campaign for the tournament organizer.
Originally published in Hambrick, M. E., Mahoney, T. Q., & Calabrese, R. (2012). Clicking for a cause: Using social media campaigns to drive awareness for golf tournaments and charitable organizations. Case Studies in Sport Management, 1(1), 1-6. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Internet marketing; Nonprofit organizations -- Marketing; Social media; Charity golf tournaments